Strategi Guru PAI dalam Meningkatkan Hafalan Al-Qur’an melalui Program Tahfidz - Ayu Anggraeni, Darsla Dyah; Wuryanto, Edy; Ahmadi, Ahmadi (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KH. EZ. Muttaqien Purwakarta, 2024)
This study aims to identify the strategies employed by PAI (Islamic Education) teachers to enhance Al-Qur'an memorization through the Tahfidz program at SMPN 1 Sambit, as well as to identify the supporting and hindering factors of these strategies. The research method used is a descriptive qualitative approach. The type of research conducted is a case study. Data collection techniques include interviews, observations, and documentation. Data analysis is performed through data condensation, data presentation, and drawing conclusions or verification. The results of the study indicate that the strategies employed by PAI teachers to enhance Al-Qur'an memorization in the Tahfidz program involve the implementation of guidance strategies using the jama’ and muroja’ah methods.